A Double-blind, Randomized Phase 2 Controlled Trial of Intradermal Hepatitis B Vaccination With a Topical Toll-like Receptor 7 Agonist Imiquimod, in Patients on Dialysis. (18th June 2020) - Hung, Ivan Fan-Ngai; Yap, Desmond Yat-Hin; Yip, Terence Pok-Siu; Zhang, Ricky Ruiqi; To, Kelvin Kai-Wang; Chan, Kwok-Hung; Tang, Sydney Chi-Wai; Lui, Sing-Leung; Levin, Yotam; Kochba, Efrat; Lau, Johnson Yiu-Nam; Yuen, Man-Fung; et al.
Abstract: Background: Patients on dialysis are hyporesponsive to the hepatitis B virus vaccines (HBVv). We examined intradermal (ID) HBVv Sci-B-Vac, with topical Toll-like receptor 7 (TLR7) agonist imiquimod pretreatment in dialysis patients. Methods: We enrolled and prospectively followed adult patients on dialysis between January 2016 and September 2018. Eligible patients were randomly allocated (1:1:1) into 1 treatment group, topical imiquimod cream followed by ID HBVv (IMQ + ID); and 2 control groups: topical aqueous cream (placebo) followed by ID HBVv (AQ + ID) or topical aqueous cream followed by intramuscular HBVv (AQ + IM). The primary endpoint was the seroprotection rate (hepatitis B surface antibody ≥10 mIU/mL) at 52 weeks. Results: Ninety-four patients were enrolled, among which 57.4% were previous nonresponders. Seroprotection rate was significantly better at week 52 for the IMQ + ID group with 96.9% compared to 74.2% and 48.4% for AQ + ID and AQ + IM groups, respectively ( P < .0001). The geometric mean concentration was significantly higher at week 52 for the IMQ + ID group: 1135 (95% confidence interval [CI], 579.4–2218.2) mIU/mL, compared to 86.9 (95% CI, 18.5–409.3) mIU/mL and 7.2 (2.0–26.5) mIU/mL for the AQ + ID and AQ + IM groups, respectively ( P < .0001). IMQ + ID vaccination (odds ratio, 3.70 [95% CI, 1.16–11.81]; P = .027) was the only factor independently associated with higher 52-week seroprotection rate. Adverse reaction was infrequent. Conclusions: Pretreatment with topical imiquimod before ID HBVv Sci-B-Vac was safe with favorable seroprotection in dialysis patients. Clinical Trials Registration: NCT02621112. Abstract : This study demonstrated that topical imiquimod (TLR7 agonist) before intradermal hepatitis B vaccination was safe, with significantly better seroprotection than intradermal or intramuscular vaccination alone up to 78 weeks. This strategy improved prevention against hepatitis B infection in dialysis patients.